Additional heart sounds during early diastole in a patient with hypertrophic cardiomyopathy and atrioventricular block - Konishi, Eiko (J Cardiol Cases, 2015)
A third heart sound (S3) and a fourth heart sound (S4) are similarly perceived as low-pitched sounds and can be difficult to distinguish in some conditions, such as tachycardia or arrhythmia. We report a case with hypertrophic cardiomyopathy and Wenckebach second-degree atrioventricular block, in which the S4 was initially misdiagnosed as an S3 on auscultation and later confirmed using a phonocardiogram with an apexcardiogram. Interestingly, the amplitude of the S4 dynamically and regularly fluctuated in proportion to the interval between the S4 and the preceding ventricular contraction. These findings were associated with transmitral inflow patterns assessed by Doppler echocardiography, highlighting the importance of not only transmitral A but also E waves for the amplitude of S4 in patients with arrhythmias. <Learning objective: A fourth heart sound could be difficult to diagnose and dynamically fluctuate in amplitude in patients with arrhythmias, such as Wenckebach second-degree atrioventricular block. These findings are likely to be associated with changes in transmitral inflow patterns assessed by Doppler echocardiography.>